Bahasa Inggtris Bahasa Inggtris: Case Study of the Versant 3100i Printing Machine at CV XYZ - Yamin, Iqbal; Suharto, Nurlita Pratiwi; Satriaji, Tegar Bayu; Sinur, Valeri Vela; Zulkarnain, Zulkarnain (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2025)
This study examines machine performance inefficiencies in a digital printing production system by applying the Overall Equipment Effectiveness (OEE) method to the Versant 3100i digital printing machine at CV XYZ. The objective of this research is to evaluate machine effectiveness, identify dominant sources of production losses, and analyze their root causes to support operational performance improvement. An integrated analytical approach is employed by combining OEE measurement, Six Big Losses analysis, and Fishbone Diagram techniques to systematically diagnose machine performance issues. The results show that the average OEE value of the Versant 3100i machine is 82.92%, which remains below the international benchmark of 85%, indicating that machine performance has not yet reached an optimal level. Analysis of the Six Big Losses reveals that Reduced Speed is the most significant contributor to performance loss, accounting for 36.24% of total losses. Further analysis using a Fishbone Diagram indicates that Reduced Speed is mainly caused by human-related factors and the absence of standardized Standard Operating Procedures (SOPs). Based on these findings, targeted improvement strategies are proposed, including structured operator training, the implementation of standardized operating procedures, and the strengthening of quality control mechanisms. This study demonstrates that the integrated use of OEE, Six Big Losses, and Fishbone Diagram analysis is effective in identifying priority improvement areas and formulating practical improvement strategies. The proposed approach can be applied by manufacturing companies to enhance machine effectiveness and operational efficiency, particularly in digital printing production environments.